Prevalence of Hypertension in Ghana: Analysis of an Awareness and Screening Campaign in 2019. Issue 16 (August 2022) - Tannor, Elliot Koranteng; Nyarko, Obed Ofori; Adu-Boakye, Yaw; Owusu Konadu, Saabea; Opoku, Gilda; Ankobea-Kokroe, Frank; Opare-Addo, Mercy; Appiah, Lambert Tetteh; Amuzu, Evans Xorse; Ansah, Gilgal Justice; Appiah-Boateng, Kate; Ofori, Emmanuel; et al.
Introduction: Hypertension is an important public health menace globally and in sub-Saharan Africa. The prevalence of hypertension is on the rise in low- and lower-middle-income countries (LMIC) such as Ghana. This rise led to the adoption of the May Measurement Month (MMM) initiative, a global blood pressure screening campaign. We aimed to create awareness and present the findings of the 2019 MMM screening campaign in the Ashanti region of Ghana. Methods: Ghana was 1 of 92 countries that participated in this global community-based cross-sectional study in May 2019. Participants (⩾18 years) were recruited by opportunistic sampling. The blood pressures of participants were measured 3 times and the mean of the last 2 was used for the analysis. Summary statistics were used to describe the data. Simple and multiple logistic regression models were used to determine the predictors of hypertension. Results: We screened 3080 participants with a mean age of 39.8 ± 16.8 years. The prevalence of hypertension was 27.3% among participants. Two-thirds of the hypertensives were unaware of their condition and only 49.5% of participants with a history of hypertension on medication were controlled. Predictors of hypertension in a multiple logistic regression were increasing age (OR = 1.05 (CI 1.04-1.06), P  < .001) and high body mass index (OR = 1.06 (1.02-1.10), P  = .005). Conclusion: The MMM initiative is highly commendable and of huge public health importance in LMICs like Ghana. Population-based health programs such as the MMM initiative is encouraged to shape appropriate public health policies to reduce the prevalence of hypertension.